Towards improved menstrual health: The impact of period products on reproductive tract infections - Karan Babbar; Manini Ojha (Global Labor Organization (GLO), 2025)
We examine the impact of usage of period products and reproductive tract infections (RTI) utilizing the National Family Health Survey-5 conducted in 2019-21 for India. Exploiting the exogenous variation in the average exposure of women in neighbouring households to television, we utilize an Instrumental Variable (IV) approach to address the endogeneity concerns present in an OLS framework. Conditional on comprehensive set of controls, we find that usage of period products reduces the likelihood of contracting any form of RTI by 16 percentage points. Our results are robust to various sample restrictions, alternative methods of estimation and the inclusion of additional controls. We also estimate the bounds of our effects by assuming the IV to be plausibly exogenous, where we relax the exogeneity condition. Policy implications suggest that enhancing access to information on menstrual health and hygiene through television could be an effective strategy to promote the adoption of hygienic practices and reduce RTIs. While the heterogeneity analysis indicates that the decline in RTI attributed to period products is pervasive across caste, class and wealth levels, the effect for rural women and those in the age group of 20-24 years highlights the need of reaching these populations with information and support.
Keywords: 330; Reproductive Tract Infections; Period Products; Menstruation; Menstrual Health and Hygiene; NFHS-5; India